PENYULUHAN PEMANFAATAN LAHAN KOSONG SEBAGAI UPAYA PENINGKATAN KETAHANAN PANGAN MASYARAKAT DESA KABINUANG KECAMATAN DAMPAL UTARA - Nur Fadilah; Ade Indah Puspita Sari; Fandi Ahmad; Hayatudin Hayatudin (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Food security is crucial in improving community welfare, particularly in rural areas dependent on the agricultural sector. However, much vacant land remains underutilised, potentially leaving it unused and reducing local food availability. To address this challenge, a community service program, including outreach and mentoring on vacant land utilisation, was implemented in Kabinuang Village, North Dampal District, from July to August 2025. The objective of this program was to provide education, training, and mentoring to the community in managing vacant land into productive land through the cultivation of horticultural crops. The methods used included land observation, cultivation technique training, monitoring activity results, and a descriptive approach. The activity results showed an increase in community knowledge and skills in managing vacant land and establishing several productive gardens as pilot projects in the village. This program had a positive impact on meeting household food needs and increasing income, strengthening the value of mutual cooperation, and creating a more sustainable environment. Therefore, this activity is expected to be the first step in the sustainable use of vacant land to support local food security and the welfare of the Kabinuang Village community.